Establecimiento de ritmos de actividades de las lagartijas diurnas(Sauria) en diferentes condiciones metereológicas en la ESPAM MFL - Centeno Morales, Víctor Alfonso (2016)
Saurians are an important vertebrate group in most ecosystems, moreless, their activity patterns have not been studied accurately in forests of Ecuador. This research stood as an objective to establish the activity patterns of diurnal lizards (Saurians) in different weather conditions in the Agriculture Polytechnic School of Manabí Manuel Félix López (0° 49' 10” S, 80° 10' 40” W, 15 msnm). The walk transect method was used to evaluate daily activity patterns. Hours rangers were stablished at 7:00 am, 10:00 am, 13:00 pm, 16:00 pm, 18:00 pm. The whole monitoring record was constituted by visual records. 822 sightings were recorded in the study zone, (409 during dry season and 413 during rainy season), and were recorded four species of four different families. The database was filled on September and November, 2015 and May, 2016. Saurians studied showed the most activity at 27°C, 5.0 heliophany value. The main activity pattern corresponded to September (Dry season). The Poisson distribution was used to correlate the activity patterns with weather conditions (ambient temperature, heliophany). The activity patterns found in the Saurians are differently related with the temperature, sunlight hours.